1994
DOI: 10.1177/019262339402200409
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar Frequency of Hepatoblastomas and Hepatic Cystadenomas and Adenocarcinomas Arising in Hepatocellular Neoplasms of D2B6F1 Mice Initiated with N-Nitrosodiethylamine and Subsequently Given Aroclor-1254, Dichlorodiphenyltrichloroethane, or Phenobarbital

Abstract: Aroclor-1254 (Ar-1254) and dichlorodiphenyltrichloroethane (DDT) were compared to phenobarbital (PB) for their ability to promote hepatocellular proliferative lesions to hepatocellular adenomas and carcinomas and to hepatoblastomas in D2B6F1 male mice initiated with N-nitrosodiethylamine (NDEA). Hepatocellular neoplasms developed in all mice given NDEA and were more numerous in mice fed promoters. Multiplicities decreased in the order Ar-1254 > PB > DDT, indicating that Ar-1254 was more potent than eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…POPs are lipophilic chemicals that accumulate in adipose tissue and are associated with the risk of various chronic diseases [7], [8], [9]. The biological plausibility for our hypothesis was that experimental studies in mice reported that pretreatment with some POPs increased toxicity of important chemicals contained in cigarette smoke, like benzopyrene, dimethylnitrosamine, and N-nitrosodiethlyamine [10], [11].…”
Section: Introductionmentioning
confidence: 82%
“…POPs are lipophilic chemicals that accumulate in adipose tissue and are associated with the risk of various chronic diseases [7], [8], [9]. The biological plausibility for our hypothesis was that experimental studies in mice reported that pretreatment with some POPs increased toxicity of important chemicals contained in cigarette smoke, like benzopyrene, dimethylnitrosamine, and N-nitrosodiethlyamine [10], [11].…”
Section: Introductionmentioning
confidence: 82%
“…More than 3,000 chemicals have been identified in cigarette smoke, and many of them are both mutagenic and carcinogenic. Experimental findings on increased carcinogenicity of chemicals contained in cigarette smoking after pretreatment of some POPs strongly suggest the biological interaction between cigarette smoking and POPs (6, 7). …”
Section: Discussionmentioning
confidence: 99%
“…In experimental studies, pretreatment of PCBs or some OCPs like DDT increased genotoxicity of carcinogens like benzopyrene, dimethylnitrosamine, and N-nitrosodiethylamine, which are important components of cigarette smoke (6, 7). In fact, the chronic exposure to low dose POPs has recently been linked to various common diseases in general population (8-12).…”
Section: Introductionmentioning
confidence: 99%
“…After 2.5 weeks, mice were given Aroclor 1254 as an intraperitoneal dose at 0 (tricaprylin/corn oil, 1/4, v/v) Diwan et al (1994) examined whether Aroclor 1254 promoted NDEA-initiated tumours of the liver in groups of 30 male DBA/2NCr × C57BL/6NCr (D2B6F1) mice. At age 5 weeks, mice were injected intraperitoneally with NDEA at a dose of 0 (tricaprylin vehicle) or 90 mg/kg bw.…”
Section: (B) Aroclor 1254 (I)mentioning
confidence: 99%